Coronavirus Infection in Ferrets: Antigen Distribution and Inflammatory Response. (November 2016) - Doria-Torra, G.; Vidaña, B.; Ramis, A.; Amarilla, S. P.; Martínez, J.
Multisystemic granulomatous lesions are the most common finding in ferrets infected by ferret systemic coronavirus (FRSCV). To characterize the inflammatory response developed against this virus, lesions from 4 naturally infected ferrets were examined. Lesions were classified into the 4 known types of granulomas (granulomas without necrosis [G], granulomas with necrosis [G-N], granulomas with neutrophils [G-NL], and diffuse granulomatous inflammation [DG]). The cellular composition of the lesions was characterized on the basis of cellular morphology and immunohistochemistry using markers for T and B-lymphocytes, plasma cells, macrophages, and neutrophils. The extent and distribution of viral antigen expression was also assessed. In G lesions, macrophages were mainly located in the center of the granuloma, with a moderate number of T-lymphocytes scattered among the macrophages, plasma cells, and B-lymphocytes. G-N lesions exhibited a necrotic center surrounded by abundant macrophages, some T-lymphocytes, plasma cells, and a few B-lymphocytes. In G-NL lesions, there was a central area dominated by neutrophils with low numbers of macrophages, plasma cells, and lymphocytes. DG presented similar cell proportions, but distributed evenly throughout the lesions. FRSCV was expressed in G, G-NL, G-N, and DG, with decreasing numbers of immunoreactive cells. This study reveals the important role of macrophages in the inflammatory response of ferrets against the virus and the variable proportions of leukocytes among different types of lesions, indicating their variable age. The results also confirm the similarities of the disease in ferrets to feline infectious peritonitis.